Culture, Politics, and Money Among the Yoruba. - Adebayo, Akanmu (Taylor and Francis, 2018)
"This masterful book investigates and analyzes several aspects of money among the Yoruba of Nigeria. Falola and Adebayo explore the origin, philosophy, uses, politics, and problems of acquiring and spending money in Yoruba culture. No prior book exists on this aspect of a major ethnic group in Africa with established connections with the black Diaspora in North America and the Caribbean. Conceived so that each chapter may be read individually, the volume is divided into three parts. Part 1, "Money and Its Uses," focuses on the transition from barter to cowry currency, the idealistic and pragmatic views of money, the impact of monetization on social stratification, accumulation among members of the elite, and the development of savings, banking, and credit institutions. Part 2, "Money and Its Problems," investigates the social, political, and cultural problems of money, including money-lending, theft, counterfeiting, and corruption. Part 3, "Money and Oil Economy," assesses the impact of the oil industry on the Nigerian state and examines both the positive and negative effects of oil money on Yoruba economy, society, and spending. Concluding chapters detail efforts to arrest the crisis that followed the economic slump after the oil boom and led to the adoption of the Structural Adjustment Program, and also evaluate the effects of currency devaluation on personal and communal responsibilities and social payment. Culture, Politics, and Money Among the Yoruba is timely in view of ongoing political and economic changes in Africa. It will be of interest to economists, sociologists, and African studies specialists."--Provided by publisher.